Greening the start-up of reactive distillation: A combined experimental and LCA study from cold and empty state - Sharma, Nikhil; Sonkusare, Shubham; Moudgalya, Kannan M.; Shah, Sunil (Frontiers in Chemical Engineering, 2025)
Reactive distillation is a process intensification technique that merges reaction and separation in one unit, reducing equipment count and energy use. It boosts conversion by continuously removing products, making it ideal for equilibrium-limited systems. Reactive distillation is predominantly used for industrial processes such as esterification, etherification, hydrolysis, etc. Start-up of reactive distillation columns is difficult, owing to possibility of multiple steady states and runaway reactions resulting in increased start-up times and associated environmental impact. This work addresses optimal start-up of a methanol esterification by reactive distillation to reduce start-up time and energy. Novel scheduling framework developed by the authors is leveraged to manage variable structure of the model equations required for simulating and optimizing the start-up operation. The startup process is validated with experimental studies in a pilot plant. This method is compared with the traditional start-up process. Environmental impact associated with the start-up phase of methanol esterification in reactive distillation is assessed using a detailed cradle-to-gate LCI and applying the ReCiPe 2016 Mid-point (H) methodology. The optimal start-up demonstrates a 64% reductions in start-up time compared to traditional start-up, which significantly reduces environmental impacts. Key improvements in emissions included a 68% decrease in GWP, 56% reduction in fossil depletion, and 69% reduction in human toxicity when compared with the traditional method. These benefits were driven by reduced energy consumption and elimination of raw material loss during transient operation. The results highlight the environmental and operational advantages of optimal RD startup strategies and emphasize the need to include transient phases in LCA models. This approach supports sustainable process design and aligns with decarbonization goals in chemical manufacturing.